SIMBOL SIMBOL BUDAYA DALAM KERIS NAGA KAMARDIKAN KARYA MPU PATHOR RAHMAN - Anggraini, Riska Ajeng; Fianto, Achmad Yanu Alif; Riqqoh, Abdullah Khoir (Jurnal Art Nouveau, 2014)
Indonesia is one country that has a lot of cultural diversity include Anthropology , Sociology and Art . All the cultural diversity ancestors inherited from generation to generation to the next generation . One of the works of art and culture that still exist and persist until today is the work of craft art in the form of a dagger , where the artwork has a meaning and philosophy terms of the form to its usefulness . With the development of times , this dagger turns into a work of art that has a lot of meaning in the philosophy of disclosure , the translation of symbols and expectations , in other words, a keris is a manifestation of the prayer and hope of sipencipta and sipemakainya . Kris kris is often called " Esoteric " . At this time the master began to freely create shapes dagger , which had not followed the grip is standard . By using semiotic Roland Barthes , the dragon dagger Kamardikan a reflection of the attitude of the authoritative leader , gentle and wise . All the epitome of leadership is implied in the form of a dragon s eyes are sharp and rounded as a transformation of the form of an eagle eye , the presence of which is a transformation sumping shape of the human ear that reflects the attitude of the leader or ruler who need sharp hearing . Overall, this Kamardikan dragon dagger gives the impression of prestige and soft for the owner as well as create a high image for the owner due to the difference ornament often creates caste , dragon dagger ornaments on the use of jasmine flower motifs that reflect the personality of a gentle nature .